Undiagnosed Hepatocellular Carcinoma Presenting as Nasal Metastases - Hassen Mohammed; Rashid Sheikh; Waheed Rahman; Sally Sheta; Zeynel Dogan (Case Reports in Otolaryngology)
Hepatocellular carcinoma (HCC) is a primary malignancy of the liver with up to half of cases suffering from extrahepatic metastasis in the later stages of the disease. Commonly reported and encountered metastatic sites include the lymph nodes, lung, bone, and adrenal glands. This is an effort to throw a spotlight on a rare case of metastatic HCC which presented to us as two distinct lesions in the nose. It focuses on the presentation and the steps that were taken to reach this rare and unusual diagnosis. It sparks interest from a clinical and histopathology perspective. Our cynosure is the findings of the case coupled with a probe on the possible routes of spread of HCC to sinonasal region.